Pengaruh Kebijakan Dividen, Kebijakan Utang, dan Ukuran Perusahaan Terhadap Nilai Perusahaan (Studi Empiris Pada Perusahaan Yang Terdaftar Dalam Jakarta Islamic Index di Bursa Efek Indonesia 2020-2022) - Musfitria, Anessa; Budiana, Indra (Penerbit Yayasan Daarul Huda Kruengmane, 2024)
This research was conducted to see the influence of dividend policy, debt policy and company size on company value. The sample consisted of 9 companies listed on the Jakarta Islamic Index for 2020-2022. Data analysis was carried out using the multiple linear regression method with the help of SPSS 24. The research results show that dividend policy has no effect on company value, while debt policy and company size have an effect on company value.